2015
DOI: 10.1093/mnras/stv1097
|View full text |Cite
|
Sign up to set email alerts
|

The rise-time of Type II supernovae

Abstract: We investigate the early-time light-curves of a large sample of 223 type II supernovae (SNe) from the Sloan Digital Sky Survey and the Supernova Legacy Survey. Having a cadence of a few days and sufficient non-detections prior to explosion, we constrain rise-times, i.e. the durations from estimated first to maximum light, as a function of effective wavelength. At restframe g ′ -band (λ eff = 4722Å), we find a distribution of fast rise-times with median of (7.5 ± 0.3) days. Comparing these durations with analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
148
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 130 publications
(167 reference statements)
21
148
2
1
Order By: Relevance
“…The results of Gonzalez-Gaitan et al (2015), based on comparisons with the analytical models of Nakar & Sari (2010) and hydrodynamical models of Tominaga et al (2009), are in agreement with the above, i.e., that the progenitor radii are too small when compared with the expected radii of Type II-P/L SNe. On this basis, Gonzalez-Gaitan et al (2015) conclude that temperatures of red supergiant stars are underestimated, or that mixing length prescriptions used in stellar evolution models are to blame.…”
Section: Rise Times Of Sne With Direct Progenitor Detectionssupporting
confidence: 77%
See 1 more Smart Citation
“…The results of Gonzalez-Gaitan et al (2015), based on comparisons with the analytical models of Nakar & Sari (2010) and hydrodynamical models of Tominaga et al (2009), are in agreement with the above, i.e., that the progenitor radii are too small when compared with the expected radii of Type II-P/L SNe. On this basis, Gonzalez-Gaitan et al (2015) conclude that temperatures of red supergiant stars are underestimated, or that mixing length prescriptions used in stellar evolution models are to blame.…”
Section: Rise Times Of Sne With Direct Progenitor Detectionssupporting
confidence: 77%
“…On this basis, Gonzalez-Gaitan et al (2015) conclude that temperatures of red supergiant stars are underestimated, or that mixing length prescriptions used in stellar evolution models are to blame. While this may indeed be the case, we emphasize that the very useful, but still simplistic framework considered both here and in Gonzalez-Gaitan et al (2015), serve mainly to indicate relevant trends, and that factors such as the explosion energy to ejecta mass ratio will strongly influence the actual rise time.…”
Section: Rise Times Of Sne With Direct Progenitor Detectionsmentioning
confidence: 99%
“…Barbon, Ciatti & Rosino 1979), types II-P and II-L are now more commonly thought to occupy a continuum of different levels of mass loss primarily influenced by the initial mass of the progenitor (e.g. Anderson et al 2014;Sanders et al 2015;González-Gaitán et al 2015). Type IIn ('narrow lines') SNe are characterized by the presence of a dense circumstellar medium (CSM) at the time of explosion, resulting in strong interaction between the SN ejecta and the CSM (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent availability of large samples of SN II light curves (e.g., Arcavi et al 2012;Anderson et al 2014;Faran et al 2014aFaran et al , 2014bGonzález-Gaitán et al 2015;Sanders et al 2015), there is little high-quality data in the literature against which to test predictions (e.g., Nakar & Sari 2010;Rabinak & Waxman 2011, NS10, RW11) regarding early-time light curve behavior in the ultraviolet (UV) and optical bands. Rabinak & Waxman (2011) showed that it is possible to deduce the progenitor star radius (R * ) and energy per unit mass (E/M) from the early UV light curve.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gall et al (2015) and González-Gaitán et al (2015) compared large samples of SNII light curves to RW11/NS10 shock-cooling models. Both papers compared SN rise times to rise times derived from shock-cooling models: Gall et al (2015) used r-band data, while González-Gaitán et al (2015) compared multi-band photometry.…”
Section: Introductionmentioning
confidence: 99%